Peran Marger Bank Syariah di Indonesia dalam Memenuhi Kebutuhan Industri Halal - Harisah Harisah; Wasilatur Rohmaniyah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The Indonesian government has implemented a number of policies to assist the Islamic business sector in the country. One of these methods is to undertake a merger of Islamic financial institutions. This measure is a significant strategy, and it is the first in Indonesia, to increase people's preferences for sharia-compliant transactions while also advancing Indonesia's position as the world's leading Islamic banking. The following study was prepared using qualitative methods, including a review of the literature, and it used many government policies as the primary data in order to analyze the role of Islamic bank mergers in Indonesia, particularly in terms of meeting the demands of Indonesia's halal industry. It is discovered in this study that Indonesia's Halal Industry represents an opportunity to drive economic improvement in the community. This is due to the large number of consumers of halal products in Indonesia, combined with the potential of a very dominant community. As a result of this merger, financial institutions will be positioned as one of the forums for supporting the halal industry, particularly in the capital sector. In addition to providing a forum for industry players, the merger of Islamic banks provides a forum for the community to meet their needs through the development of financial inclusion, which is carried out by the banks that have merged, allowing people from all walks of life to easily access sharia-compliant banking services.Keywords: Margers; Islamic Bank; Halal industry AbstrakDalam mendukung sektor ekonomi syariah di Indonesia ada beberapa strategi yang dilakukan pemerintah. Salah satunya dengan melakukan marger bank syariah. Tindakan ini merupakan strategi yang sangat besar dan pertama di Indonesia untuk mendongkrak preferensi masyarakat dalam bertransaksi sesuai syariah dan memajukan keuangan syariah Indonesia terdepan di dunia. Dengan demikian, kajian ini ditulis dengan menggunakan metode kualitatif dengan kajian kepustakaan dan menjadikan beberapa kebijakan pemerintah sebagai data utama dalam menganalisa peran marger bank syariah di Indonesia terutama dalam memenuhi kebutuhan industri halal di Indonesia. Penelitian ini menemukan bahwa industri halal di Indonesia menjadi peluang penggerak peningkatan ekonomi di masyarakat, karena besarnya konsumen produk halal di Indonesia dengan potensi masyarakat yang sangat mendominasi sehingga lembaga keuangan dengan hasil marger ini menjadi salah satu wadah untuk mendukung industri halal terutama dalam sektor modal. Selain untuk pelaku industri, marger bank syariah juga menjadi wadah bagi masyarakat dalam memenuhi kebutuhan dengan pengembangan inklusikeuangan yang dilakukan oleh bank yang sudah dimarger, sehingga semua lapisan masyarakat dengan mudah mendapatkan layanan bank syariah.Keyword: Marger; Bank Syariah; Industri halal